The Macrotextured Implant Recall: Breast Implant–Associated-Anaplastic Large Cell Lymphoma Risk Aversion in Cosmetic and Reconstructive Plastic Surgery Practices. (16th June 2022) - Mankowski, Peter; Carr, Matthew; Cherukupalli, Abhiram; Bovill, Esta; Lennox, Peter; Brown, Mitchell H; Carr, Nicholas
Abstract: Background: The recall of Allergan Biocell (Irvine, CA) devices due to the association between anaplastic large cell lymphoma (ALCL) and macrotextured breast implants means that plastic surgeons are faced with the challenge of caring for patients with these implants in situ. Cosmetic and reconstructive surgeons have been contacting affected patients to encourage them to follow up and discuss the most appropriate risk-reduction strategies. Objectives: The aim of this study was to evaluate patient concerns about the risk of breast implant–associated ALCL (BIA-ALCL) and to compare management differences between cosmetic and reconstructive patients. Methods: A retrospective review was performed of 432 patients with macrotextured implants who presented to clinic after being contacted (121 reconstructive and 311 cosmetic). These records were analyzed for their presenting concerns, surgery wait times, and management plans. Statistical analysis was performed to compare the cohorts, and odds ratios (ORs) were computed to determine the association between patient concerns and their choice of management. Results: After consultation, 59.5% of the reconstructive cohort and 49.5% of the cosmetic cohort scheduled implant removal or exchange. The reconstructive population had a higher rate of ALCL concern (62.7%); however, both cohorts had a significant OR, demonstrating an expressed fear of ALCL likely contributed to their subsequent clinical management (OR cosmetic, 1.66; OR reconstructive, 2.17). Conclusions: Although the risk of ALCL appears to be more concerning to the reconstructive population, both cohorts were equally motivated to have their implants removed. Informing patients about their ALCL risk is crucial to ensure a patient-supported risk reduction plan. Level of Evidence: 2: